Naproxen-induced thrombocytopenia. Issue 4 (1st October 2020) - Sahu, Nitasa; Roy, Justin; Vunnam, Rama; Golamari, Reshma; Jain, Rohit
Abstract: Thrombocytopenia has many mechanisms with broad differentials. A detailed history and physical, with timely diagnostic testing, is necessary to parse out the underlying etiology. Clinicians should maintain a high suspicion for drug-induced thrombocytopenia when there is an acute drop in the platelet level after exposure to commonly implicated drugs. Drug-induced thrombocytopenia is not well defined, as reporting is voluntary and not critically reviewed. Oftentimes, the culprit is not the drug itself, but a drug metabolite, which is difficult to prove with drug-dependent antibody testing. Here we present a case where naproxen led to hemarthrosis secondary to drug-induced thrombocytopenia.